Effect of growth conditions on production of green fluorescent protein from escherichia coli fermentation - Malini, Subramaniam (2014)
Effect of growth conditions (temperature, agitation rate and working volume) on production of enhanced green fluorescent protein (EGFP) from Escherichia coli (E.coli) fermentation was studied in this research. An improved growth conditions are needed to maximize the functional EGFP production. Preparation of cell culture was done by transferring E. coli strain BL21 (DE3) carrying plasmid pRSETEGFP to agar plate by streaking method and incubated at 30°C for 18 hr. Inoculum was prepared from a single colony of E.coli from agar plate. Fermentation of batch cultures were carried out in Erlenmeyer flasks inoculated with inocula [5% (v/v)]. The process variables include temperature, agitation rate and working volume were varied throughout the batch fermentation by using one factor at a time method. During the cultivation process, samples were taken from Erlenmeyer flask to measure cell biomass and EGFP concentrations. Cell biomass concentration was determined based on the culture absorbance using spectrophotometer and EGFP concentration was determined using gel-based imaging method. The results obtained shows that EGFP production by E.coli decreases as the working volumes was increased from 20 to 50%. However, when the agitation rate was increased from 100 to 250 rpm, it subsequently increases the yield of EGFP and cell concentration. Suitable temperature (30°C) enables E.coli to grow well and produce higher amount of functional EGFP. Consequently, functional EGFP production decreased at low temperature (<30°C). At higher temperature (> 30°C) also resulted in a decrease of EGFP and biomass production due to protein aggregation into inclusion bodies. In conclusion, the yield of functional EGFP was highest in shake flask fermentation under condition, working volume of 20%, agitation rate of 200 rpm and temperature of 30°C with 0.04, 0.061 and 0.06 g/L respectively